Smart nutrision hydroponic mix Microcontroller-based system with solar power plant integration - Syaifullah Ali; Basrah Pulungan, Ali (Journal of Industrial Automation and Electrical Engineering, 2025)
Indonesia's agricultural sector faces the challenges of climate change and land constraints that drive the need for sustainable agricultural technology innovation. This research designed a Deep Flow Technique (DFT) hydroponic system based on Arduino Mega 2560 which is integrated with a Solar Power Plant (PLTS). The system uses a DFRobot TDS sensor for nutrient monitoring, an HC-SR04 ultrasonic sensor for water level detection, an ACS712 voltage and current sensor for electrical monitoring, and an I2C LCD for the display. The integration of solar power with solar panels, MPPT, and batteries provides sustainable energy. The test results showed that the TDS sensor had an accuracy with an error of 1.38%-41.11%, the ultrasonic sensor showed good reading consistency, and the electrical sensor gave the results according to the reference. Testing of the overall system proves the integration is successful with real-time monitoring capabilities and automatic controls. The solar power system has succeeded in providing stable energy for independent operations. The research resulted in an automated hydroponic prototype that improves production efficiency with the support of renewable energy.